Production efficiency and the role of collective actions among irrigated rice farms in Northern Thailand. - Christopher Llones; Panya Mankeb; Unggoon Wongtragoon; Suneeporn Suwanmaneepong (International Journal of Agricultural Sustainability, 2022)
The idea of shared irrigation management is expected to result in a better production outcome for farmers. However, there is little evidence of whether collective action participation leads to a higher level of production efficiency. Using cross-sectional survey data from irrigated rice farms in Northern Thailand, we found that a higher level of production efficiency is associated with higher participation in collective action. At the same time, engagement in collaborative works such as irrigation maintenance, group meetings, conflict resolution, and policy adherence has a marginal effect on farmers’ efficiency. Our findings suggest that complementing existing efforts in addressing irrigation issues with efforts to mobilize collective actions among farmers leads to an improved on-farm outcome.
Keywords: Agricultural Innovations and Practices; Agricultural risk and resilience; Water resources management and optimization